2016
DOI: 10.1002/anie.201610828
|View full text |Cite
|
Sign up to set email alerts
|

Fine Control of the Redox Reactivity of a Nonheme Iron(III)–Peroxo Complex by Binding Redox‐Inactive Metal Ions

Abstract: Redox-inactive metal ions are one of the most important co-factors involved in dioxygen activation and formation reactions by metalloenzymes. In this study, we have shown that the logarithm of the rate constants of electron-transfer and C-H bond activation reactions by nonheme iron(III)-peroxo complexes binding redox-inactive metal ions, [(TMC)Fe (O )] -M (M =Sc , Y , Lu , and La ), increases linearly with the increase of the Lewis acidity of the redox-inactive metal ions (ΔE), which is determined from the g v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 66 publications
2
49
0
Order By: Relevance
“…Due to a slight pseudosymmetryt owards the space group Pbca,t here are two molecules with similar bond lengthsp resenti nt he unit cell. The arithmetic mean of the OÀOb ond lengths of the two molecules [O7ÀO8 1.334 (7) and O20ÀO21 1.324 (7) ]p resent in the unit cell, namely 1.33 ,i sa lmosti dentical to that determined for 2 [1.334(4) ]and rathersimilar to the OÀOd istance calculatedm erely for O 2 À· ÀNa + (1.34 ). [15] The coordination sphereo fe ach sodium ion in 5·THF is saturated by two THF molecules.…”
Section: Influence Of the Alkali Metal Ions On The Spectroscopic And supporting
confidence: 53%
See 3 more Smart Citations
“…Due to a slight pseudosymmetryt owards the space group Pbca,t here are two molecules with similar bond lengthsp resenti nt he unit cell. The arithmetic mean of the OÀOb ond lengths of the two molecules [O7ÀO8 1.334 (7) and O20ÀO21 1.324 (7) ]p resent in the unit cell, namely 1.33 ,i sa lmosti dentical to that determined for 2 [1.334(4) ]and rathersimilar to the OÀOd istance calculatedm erely for O 2 À· ÀNa + (1.34 ). [15] The coordination sphereo fe ach sodium ion in 5·THF is saturated by two THF molecules.…”
Section: Influence Of the Alkali Metal Ions On The Spectroscopic And supporting
confidence: 53%
“…In previous studies performed by Bae et al. on an iron peroxo complex, a close correlation between the reactivity and the Lewis acidity of the added metals was found . However, such a clear correlation of the reactivity with the Lewis acidity was unlikely to be observed for the chromium superoxide series described above.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…[19] As imilar influence of Lewis acidity on the rates of electron transfer from bromoferrocene to nonheme iron(III)-peroxo complexes binding RE 3+ ions was reported. [20] (Figure 3a nd Table S10). Computed separations of these binary mixtures showed that the RE-TriNOx compounds with higher homogeneous oxidation rates were enriched in the oxidized fraction and those with lower homogeneous oxidation rates in the unoxidized fraction.…”
mentioning
confidence: 99%